2006
DOI: 10.1073/pnas.0606449103
|View full text |Cite
|
Sign up to set email alerts
|

The voltage-dependent anion channel, a major component of the tRNA import machinery in plant mitochondria

Abstract: In plants, as in most eukaryotic cells, import of nuclear-encoded cytosolic tRNAs is an essential process for mitochondrial biogenesis. Despite its broad occurrence, the mechanisms governing RNA transport into mitochondria are far less understood than protein import. This article demonstrates by Northwestern and gel-shift experiments that the plant mitochondrial voltage-dependent anion channel (VDAC) protein interacts with tRNA in vitro. It shows also that this porin, known to play a key role in metabolite tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
99
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 39 publications
3
99
0
Order By: Relevance
“…In terms of the involvement of protein factors in tRNA import, the VDAC is important in plants (Salinas et al 2006), but establishing its specific role will require further exploration. In light of our knowledge of the tRNA Lys import in yeast, the placement of the RIC among the inner mitochondrial membrane proteins in L. tropica is not unprecedented (Mukherjee et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the involvement of protein factors in tRNA import, the VDAC is important in plants (Salinas et al 2006), but establishing its specific role will require further exploration. In light of our knowledge of the tRNA Lys import in yeast, the placement of the RIC among the inner mitochondrial membrane proteins in L. tropica is not unprecedented (Mukherjee et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, for instance, the voltagedependent anion channel (VDAC) in the outer membrane was shown to play a crucial role for import in vitro (Salinas et al 2006). However, the homologous protein is dispensable for import in T. brucei (Pusnik et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In yeast (Saccharomyces cerevisiae), the cytosolic tRNA for Lys is bound specifically by glycolytic enolase and transferred to the precursor of the mitochondrial lysyl-tRNA synthetase at the mitochondrial surface, after which it is cotransported through the protein import apparatus (Tarassov et al, 1995;Sepuri et al, 2012). In plants, the VDAC and components of the protein import apparatus such as Tom20 and Tom40 have been shown to be involved in tRNA import (Salinas et al, 2006). Furthermore, the addition of nucleic acid-binding proteins improves tRNA import rates in vitro, suggesting the involvement of as yet unidentified cytosolic factors.…”
mentioning
confidence: 99%
“…Subsequently, an in vitro tRNA uptake assay was established, which showed the uptake of cytosolic tRNA into isolated mitochondria (Sieber et al, 2011). Further studies have suggested that there is cooperation among components of the protein import translocase of the outer membrane (TOM) and Porin/voltage-dependent anion channel (VDAC), although specific proteins dedicated for the import of tRNA have yet to be identified (Salinas et al, 2006).…”
mentioning
confidence: 99%
“…Recently, the attachment of the lipid synthesis protein STAR to VDAC during the life cycle of a eukaryotic cell was described (Bose et al 2008). Other reports depict VDAC as part of a tRNA uptake system in plant cells (Salinas et al 2006). …”
mentioning
confidence: 99%